Optimalisasi Penyebab Keterlambatan Proyek Revitalisasi Gedung Sekolah Pascasarjana Kampus B Universitas Airlangga - Wahyudi, Agus; Dzinnur, Cilda Thesisa Ilmawan; Hamzah, Yayu Sriwahyuni (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
Delays in the Airlangga University Postgraduate school building revitalization project occurred due to design changes, weather and some invalid data. The aim objective this study is to identify the contributing components. delays and obtain the root of the problem which has the most important role in resolving work delays on a construction project for the revitalization of the postgraduate building at Arilangga University. This research began with collecting data through field surveys, and observing what factors caused delays that occurred during the execution of the building of the Arilangga University postgraduate building revitalization project. The methods for gathering data that were employed in this study are, firstly primary data and secondly secondary data. Primary data is data produced through field surveys, interviews and observations. Meanwhile, secondary data is based on literature study, information from related parties. This research uses the same data collection techniques as in research conducted by others relevant research. Interview and observational data revealed that the elements contributing to the delays in the construction of the Arilangga University postgraduate building revitalization project were: 1) design changes due to the unsuitability of the function of several building structures, 2) delays in material supplies, 3) unpredictable weather. Of the several factors causing delays Regarding this project, one could say that delays occurred in design changes and delays in material supplies